Assessment of anterior loop of mandibular canal and its implication in implant therapy - Namrata Madan Khetal; Salman Tarique Ansari; Rajvir Malik; Ashish Babanrao Lanjekar; Sanjana Jayant Jirafe; Apeksha Sanjay Gajghate (Wolters Kluwer Medknow Publications, 2022)
Context: Precise identification of anatomic structures is imperative for presurgical planning for implant installation to ensure effectiveness of procedures, especially in the region of mental foramen, and to prevent iatrogenic complications. Aims: This study aimed to assess the presence of anterior loop of mandibular canal and its approximation to the alveolar crest using cone-beam computed tomography (CBCT). Materials and Methods: CBCT scans of the patients scheduled for implant therapy in the region of mental foramen were retrospectively analyzed for the presence of anterior loop of mandibular canal. Findings were compared based upon gender and side of the mandible. Distance between the most prominent part of anterior loop of mandibular canal and the alveolar crest was measured. Results: Anterior loop of the mandibular canal was identified 66.8% of hemimandibles analyzed with the highest prevalence in the fourth decade of life. Males and females exhibited predilection toward the right and left side, respectively. The presence of anterior loop of mandibular canal is associated with reduced distance between the neurovascular bundle and alveolar crest jeopardizing the placement of standard length dental implant. Conclusion: The current study emphasizes an increased need for precise identification and preservation of anterior loop of mandibular canal in the third and fourth decades of life, especially in females.